Vesicles composed of fatty acid and N-[3-(dimethylamino)propyl]-octadecanamide: effect of fatty acid chain length on physicochemical properties of vesicles. (March 2014) - Wang, Min Hui; Kim, Jin-Chul
Abstract Background and objectives: Vesicles, recently claimed as drug delivery carriers, were prepared by taking advantage of an electrostatic interaction between the carboxylic groups of fatty acids (FAs) and the amino groups of N-[3-(Dimethylamino)propyl]-Octadecanamide (DMAPODA). The study is to find out the effect of FAs' chain length on physicochemical properties of vesicles. Methods: Decanoic acid (DA), myristic acid (MA), stearic acid (SA) and behenic acid (BA) were used as FAs. Vesicles composed of them and DMAPODA were studied about formation on microscope, calorimetric analysis, size and zeta potential. Results: On microphotographs, all of FAs could form vesicles when mixed with DMAPODA in an equi-molar ratio. However, DA/DMAPODA vesicles were disintegrated during the homogenization. Due to the asymmetry of DA/DMAPODA associate, it seems to hardly form a stable and well-packed bilayer. On thermograms, the vesicles exhibited one strong peak, indicating that FAs can be homogeneously mixed with the cationic amphiphile. The sizes of the four kinds of vesicles suspended in an aqueous solution (final pH 7.5) were in the same order (hundreds of nanometer) on microphotographs. But, on a light scattering machine, the mean size of MA/DMAPODA vesicle was measured to be much greater than those of the other vesicles, possibly because of the low absolute value of the zeta potential. In addition, the medium pH value had a significant effect on the size of BA/DMAPODA vesicle possibly because the zeta potential was strongly dependent on the pH value. Conclusion: FAs' chain length would affect the physicochemical properties of vesicles composed of them and DMAPODA.